Implant Exposure after Immediate Reconstruction for Breast Cancer - Alfred Fitoussi; Helene Charitansky; Fabien Petitperrin; Benoit Couturaud (Archives of Breast Cancer, 2016)
Background: The technique most frequently employed for breast reconstruction, either immediate (IBR) or delayed (DBR), is the insertion of a prosthesis. The placement of a foreign body always carries the risk, albeit small, of peri-prosthetic infection and exposure of the implant that necessitates its removal, signaling the temporary or permanent failure of the reconstruction.